Karakteristik Ekstrak Kulit Petai (Parkia speciosa Hassk) dengan Pelarut Ethanol 70% dan etil Asetat - Agustin Wijayanti (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
Petai peel (Parkia speciosa) is known to contain compounds that are beneficial for health. The purpose of this study was to determine the characteristics of simplicia as well as ethanol and ethyl acetate extracts of petai peel by maceration method. The research phase begins with drying, starting with the sorting process, then washing and drying with the wind dry method until the moisture content reaches 10%. After drying, the dried simplicia was reduced in size by means of a blender. After the blending process until it becomes powder, then it is sieved using a 20/40 size sieve. The simplicia powder was macerated with 70% ethanol and ethyl acetate as much as 7.5 times the weight of the simplicia for 5 days accompanied by stirring. Strained to obtain filtrate I and the dregs followed by remaceration with 70% ethanol and ethyl acetate 2.5 times the weight of the simplicia for 2 days. Screened to obtain filtrate II. Then the filtrate I and II were combined and then evaporated to produce a thick extract, then the phytochemical test was carried out. The results showed that the extraction of petai peel using the maceration method had a significant difference in the yield of the petai peel extract in two solvent variations. The yield of petai peel extract with 70% ethanol solvent was 25.88%. And the extract with ethyl acetate solvent is 4.71%.